Vascular Disease, Alzheimer's Disease, and Mild Cognitive Impairment 2020
DOI: 10.1093/oso/9780190634230.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Everyday Functioning in MCI and Dementia

Abstract: Performance of everyday activities requires the coordination of a variety of complex cognitive processes; thus, as cognition changes over time, so too does the ability to perform everyday activities. This chapter will review the extant literature on everyday functioning in healthy aging, mild cognitive impairment (MCI), and dementia from a neuropsychological perspective. The chapter first briefly reviews the various terms used to denote everyday functioning and associated difficulties/impairment. It also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although these tasks used to be performed with ease because they are routine and familiar [8], Chevignard et al found that errors occur more frequently as a person with dementia's cognition changes over time [9]. The tasks become too complex because they require coordinating multiple cognitive processes such as object selection, sequencing numerous steps, and perceptual-motor operations [9][10][11]. Therefore, people with dementia's changes in cognition prevent them from successfully executing their daily tasks [9].…”
Section: Complex Activitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although these tasks used to be performed with ease because they are routine and familiar [8], Chevignard et al found that errors occur more frequently as a person with dementia's cognition changes over time [9]. The tasks become too complex because they require coordinating multiple cognitive processes such as object selection, sequencing numerous steps, and perceptual-motor operations [9][10][11]. Therefore, people with dementia's changes in cognition prevent them from successfully executing their daily tasks [9].…”
Section: Complex Activitiesmentioning
confidence: 99%
“…Several researchers [11,19,20] have previously investigated how step-by-step technology can guide people with dementia through daily tasks.…”
Section: Guidance Through Activitiesmentioning
confidence: 99%
See 3 more Smart Citations